Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/nl103301x
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Growth of Single-Crystal Ni Nanowires onto Amorphous SiO2

Abstract: Highly oriented, single-crystal Ni nanowire arrays have been synthesized atop amorphous SiO2∥Si substrates using a single-step chemical vapor deposition method in the absence of any foreign catalyst. Electron and X-ray diffraction confirm the crystalline quality of the Ni nanowires while magnetoresistance measurements probe the magnetic response and the behavior is explained using simulation results for nanoscale, single-crystal Ni. A growth mechanism involving competing chemical, energetic, and kinetic influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Fast fabrication of patterned Ni NWs with a high degree of uniformity, long length and high density together with mass production can be demanding and important from both applicability and theoretical points of view [1,3,8,9]. Until now, a variety of methods including chemical vapor deposition, lithography, hydrothermal technique and electroplating have been employed to fabricate Ni NWs [10][11][12][13]. Amongst these approaches, the template-based synthesis of Ni NWs such as electrodeposition into porous aluminum oxide (PAO) templates has been more advantageous because of its low cost and flexibility [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Fast fabrication of patterned Ni NWs with a high degree of uniformity, long length and high density together with mass production can be demanding and important from both applicability and theoretical points of view [1,3,8,9]. Until now, a variety of methods including chemical vapor deposition, lithography, hydrothermal technique and electroplating have been employed to fabricate Ni NWs [10][11][12][13]. Amongst these approaches, the template-based synthesis of Ni NWs such as electrodeposition into porous aluminum oxide (PAO) templates has been more advantageous because of its low cost and flexibility [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From a priori NWs growth information, [7,8] we observed that the NWs had a small amount of impurities embedded at the surface. Taking this into account, we introduce an inner core region of the NW to be of uniform density and having relatively few impurities while the outer shell region has a higher density of impurities.…”
mentioning
confidence: 97%
“…1(b) with well-defined orthogonal and smooth facets. [7,8] The NWs are grown in the [001] crystallographic orientation with widths ranging from 50 nm to about 300 nm and lengths of up to 5 µm and average coverage density of between 0.1 and 0.3 NW/µm 2 . CXD in the Bragg geometry has been shown to be a powerful characterization technique for imaging of local nanoscale lattice distortions, commonly described by deformation fields, u(r) within a small crystal.…”
mentioning
confidence: 99%
“…Fabrication of Fe nanowires on yittrium-stabilized zirconia single crystal substrates by thermal CVD methods A. Kawahito, 1 T. Yanase, 2 T. Endo, 3 T. Nagahama, 3 and T. Shimada 3,a) Magnetic nanowires (NWs) are promising as material for use in spintronics and as the precursor of permanent magnets because they have unique properties due to their high aspect ratio. The growth of magnetic Fe whiskers was reported in the 1960s, but the diameter was not on a nanoscale level and the growth mechanism was not fully elucidated.…”
mentioning
confidence: 99%